Servicio al cliente en “pc soluciones” de la ciudad de Babahoyo - Bustamante Pérez, Paola Jeamilex (2022)
Customer service is one of the main pillars in the offer that is presented to the market, this, because today, due to the increase in business competitiveness, consumers have many more options to make their purchases, therefore they will have preference for those businesses that provide greater value in what they offer, being a requirement that not only the product maintains high quality standards, but also that there are more aspects to meet the needs of consumers throughout the buying process. The objective of this study is to analyze the customer service of "PC Soluciones" in the city of Babahoyo, where despite the increase in demand for technology items, the establishment does not register an increase in sales, because internal inconsistencies do not allow to meet the requirements of customers, who upon witnessing the delays in deliveries, product shortages, or even the instability of sales prices, decide to know the offers of competing companies. In order to carry out the research process, a mixed methodological approach was used, with the purpose of having available information from direct and indirect sources for its subsequent analysis, using the descriptive type of research and the deductive, analytical and bibliographic methods. It was deduced that the failures in the handling of the merchandise do not allow to satisfy the needs of the consumer during the whole purchasing process, which is a serious affection to the service of PC Soluciones, so it is important to optimize the logistic and inventory management.